Pengaruh Kompetensi Pedagogik Guru terhadap Pelaksanaan Evaluasi Pembelajaran Fiqih - Muhammad Subhan; Titin Mansurotin (Fakultas Agama Islam Universitas Billfath, 2022)
This study aims to determine the teacher's pedagogic competence in learning fiqh, to determine the implementation of learning evaluation in fiqh subjects, and to determine the effect of teacher pedagogic competence on the implementation of learning evaluation in fiqh subjects. Correlative Quantitative Research. The population in this study was 14 students and became the overall sample. Data collection using questionnaires and documentation. The data analysis technique used is Product Moment correlation. The results of this study indicate that based on data analysis of variables (X=85%) and (Y=82%). Then statistical calculations using the Product Moment correlation formula obtained significant results, namely (r count > r table 0.673 > 0.532) so that it can be said that there is an influence of pedagogic competence on the implementation of learning evaluation in fiqh lessons.